1978
DOI: 10.1021/jm00205a017
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio study of electronic factors in metabolic hydroxylation of aliphatic carbon atoms

Abstract: The monooxygenase-mediated hydroxylations of aliphatic carbon atoms are known to be regioselective for positions alpha to heteroatoms or to pi systems (aromatic rings, carbon-carbon double bonds, carbonyl groups). Ab initio calculations (STO-3G and in some cases 4-31G) were performed on model molecules, indicating that the Mulliken overlap populations (taken as indices of electron bond densities) of Calpha-H bonds being regioselectively hydroxylated are larger than Cbeta-H and Cgamma-H overlap populations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Although the exact position of metabolism in compound 3 was not determined from our metabolism studies with compound 1 , oxidation on either side of the basic piperazine nitrogen was probable, as benzylic C–H bonds and carbons adjacent to a nitrogen atom are particularly prone to oxidation by cytochrome P450 enzymes . In addition, the benzylic position of compound 1 was also predicted to be the most likely site of metabolism using MetaSite prediction software, which was consistent with literature precedent. , Therefore, we examined the effect of methyl (and trifluoromethyl) substitutions on the benzylic position and/or on the piperazine ring in the second phase of our SAR investigations as a potential means of blocking metabolism in this region of the molecule.…”
Section: Resultssupporting
confidence: 65%
“…Although the exact position of metabolism in compound 3 was not determined from our metabolism studies with compound 1 , oxidation on either side of the basic piperazine nitrogen was probable, as benzylic C–H bonds and carbons adjacent to a nitrogen atom are particularly prone to oxidation by cytochrome P450 enzymes . In addition, the benzylic position of compound 1 was also predicted to be the most likely site of metabolism using MetaSite prediction software, which was consistent with literature precedent. , Therefore, we examined the effect of methyl (and trifluoromethyl) substitutions on the benzylic position and/or on the piperazine ring in the second phase of our SAR investigations as a potential means of blocking metabolism in this region of the molecule.…”
Section: Resultssupporting
confidence: 65%
“…29 Most recently it has been demonstrated that metabolic hydroxylation of an aliphatic carbon atom showed a marked regioselectivity at the a carbon to heteratoms or systems when quantum-mechanical approaches were used. 43,44 The retention of electronic descriptors (numbers 14 and 15 of Table IV) used in this study implicitly supports this «hydroxylation hypothesis in view of the fact that these two descriptors represent the electronic properties of the N-NO group and the -carbon atom.…”
Section: Discussionsupporting
confidence: 66%
“…nitroso-A-ethylisopropy lamine wc42 A-nitrosodi-n-buty lamine 116 A-nitrosodiethanolamine wc43 A-nitrosodi-n-pentylamine 117 A, A'-dinitroso-A, A'-dimethylphthalamide wc44 A-nitroso-A-methylviny lamine nitroso-A-methyl-n-propy lamine+ c 120 2,2,6,6-tetramethyl-A-nitrosopiperidine -47 A-nitroso-A-methyl-n-but y lamine + c 121 4-terf-butyl-A-nitrosopiperidine -48 ni troso-A-methyl-rc-penty lamine + c 122 2-carboxy-A-nitrosopiperidine -49 A-nitroso-A-(2-hydroxypropyl)-n-propylamine 4-C 123 4-carboxy-A-nitrosopiperidine 50 A-nitroso-A-( 2-oxopropy l)-n-propylamine 124 nitrosoguvacoline -51 A-nitroso-A-methylbenzy lamine + c…”
mentioning
confidence: 99%
“…Under this circumstance, the intermolecular CT states may significantly contribute to the excitonic couplings via the superexchange mechanism. [51][52][53][54] Both the shortrange exchange and superexchange interactions make the relationship between the relative molecular orientation and the signs of couplings ambiguous. One thus cannot use conventional H-and J-aggregate to predict the signs of excitonic couplings.…”
Section: The Aggregation Packing Type Versus the Signs Of Excitonic C...mentioning
confidence: 99%